Corporate diversification and ceo compensation: Evidence from the moderating effect of stock ownership - Hwei Cheng Wang; Yung-I Lou; Chiulien C. Venezia; Nicole A. Buzzetto-Hollywood (e-Finanse: Financial Internet Quarterly, 2019)
The article is an attempt to assess whether Stock Ownership moderates the relationship between corporate diversification and CEO compensation. Based on agency theory, we develop the hypothesis of whether when CEOs hold a large fraction of their firms' outstanding stock, the CEOs are acting more as owners or shareholders than employees. This reduces the principal and agency relationship of agency theory, since CEOs are acting as owners rather than employees; thus the demand for further stock-based compensation is likely to be reduced because the interests of CEOs and shareholders are relatively aligned. For the purposes of this study, a sample of 2,448 CEO compensations across 1,622 firms from 1997 to 2002 was used to test several hypotheses. Corporate diversification was divided into two categories; international diversification and industry diversification. To test the hypotheses, multiple regression analysis was employed to examine stock ownership as a moderator variable on the relationship between international diversification and industry diversification and CEO total compensation with tenure, age, duality, and gender as control variables. The results indicate that stock ownership negatively and significantly influences the relationship between International diversification and CEO compensation. Additionally, the findings also confirm that stock ownership negatively and significantly influences the relationship between industrial diversification and CEO compensation.
Keywords: M4; M12; 330; CEO Compensation; Corporate Diversification; International Diversification; Industrial Diversification; Firm Performance; Investment Opportunity; Stock Ownership